Whole genome sequencing reveals virulence–mobile element linkages and phylogenetic diversity in multidrug-resistant Escherichia coli from Nigeria - Medugu, Nubwa; Aworh, Mabel Kamweli; Iregbu, Kenneth; Nwajiobi-Princewill, Philip; Hull, Dawn M.; Harden, Lyndy; Singh, Pallavi; Obaro, Stephen; Egwuenu, Abiodun; Adeboye, Faith; Egah, Ruth; Uzairue, Leonard; et al. (Frontiers in Microbiology, 2025)
BackgroundMultidrug-resistant Escherichia coli poses a critical public health threat in Nigeria, where limited genomic surveillance hinders the understanding of virulence-resistance interplay.MethodsThis cross-sectional study employed whole-genome sequencing to characterize 107 MDR-E isolates from a Nigerian tertiary hospital (2019–2020), analyzing virulence genes, mobile genetic elements (MGEs), phylogroups, sequence types (STs), pathotypes, and antimicrobial resistance (AMR).ResultsWe identified 2,021 virulence genes across nine functional categories, dominated by immune evasion (terC, 96.3%), adherence (fimH, 86%), and iron acquisition (fyuA, 63.6%). Strikingly, 81.3% of virulence genes were linked to MGEs, including MITEEc1 (75.7% of isolates) and IS30 (56.1%), with IncFII (17.8%) and Col156 (12.1%) plasmids co-harboring virulence (e.g., traJ/traT, senB) and AMR genes (e.g., blaTEM-1B). Phylogroup B2 (32.7%) dominated, exhibiting high resistance to ampicillin (97.1%) and emerging meropenem resistance (11.4%). Globally disseminated STs (ST131, ST410, ST648) carried significantly more diverse virulence genes than minor clones (p = 0.028) and were strongly associated with double-serine QRDR mutations (gyrA_S83L: 97.6%, parC_S80I: 97.6%), which correlated with more virulence genes (24.2 vs. 22.3 genes) and resistance (MAR index: 0.7 vs. 0.5) compared to minor clones. Notably, 92% (61/66) of high-risk clones harbored these mutations, versus 57% (21/37) of low-risk clones, suggesting a fitness advantage enabling major clones to sustain larger genetic cargoes. Pathotyping revealed 54.2% as extraintestinal pathogenic E. coli (ExPEC), with 72.4% of these being uropathogenic (UPEC) and 5.2% ExPEC/EAEC hybrids, alongside 43.9% atypical ExPEC strains. Hierarchical clustering demonstrated phylogroup B2’s genetic diversity and co-localization of plasmid-borne virulence/AMR genes.DiscussionThese findings underscore Nigeria’s MDR-E crisis, driven by MGE-facilitated gene transfer, hybrid pathotypes, and globally disseminated high-risk clones harboring double-serine QRDR mutations. There is continued need for robust genomic surveillance, stringent infection control measures, enhanced antibiotic stewardship, and exploration of antivirulence strategies (e.g., targeting fimH or yeh) to curb the spread of these highly adaptable pathogens in resource-limited settings and beyond.